The Study of Effect Using Cross-Promotion in Social Media Gym Towards Purchase Intention on Healthy Juice - Nissa, Camilla; Chaerudin, Rendra (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. In the last three years, Indonesia is one of the countries in Asia that has experienced an increase in awareness of healthy living. The percentage value of 73% of places in Indonesia states that healthy living is the number one issues addressed in the priorities of life. That means Indonesian society has started a healthy life by consuming healthy food and physical activity in the gym. Consume a healthy juice is also part in healthy lifestyles. In that case consumers are beginning to look for practical things to drink with consideration of taste and innovation.In the other hand, there is a problem facing in healthy juice industry in the composition, hard to expand the market, hard to reach a consumer. Than researcher considering use cross-promotion, cross promotion is one of the marketing strategies that can be used to attract customers.The purpose of this research is to see the effect of cross-promotion in social media gym and purchase intention in healthy juice. The researcher, conduct this research in Bandung area, who have respondent in age 20 until 49 years old, having activities in gym, and also using a social media Using Simple Linear Regression and quantitative method. The result is cross-promotion have a positive impact towards purchase intention.Â Keywords : cross-promotion, gym, healthy lifestle, healthy juice, purchase intention